2014
DOI: 10.1093/database/bau076
|View full text |Cite
|
Sign up to set email alerts
|

APADB: a database for alternative polyadenylation and microRNA regulation events

Abstract: Alternative polyadenylation (APA) is a widespread mechanism that contributes to the sophisticated dynamics of gene regulation. Approximately 50% of all protein-coding human genes harbor multiple polyadenylation (PA) sites; their selective and combinatorial use gives rise to transcript variants with differing length of their 3′ untranslated region (3′UTR). Shortened variants escape UTR-mediated regulation by microRNAs (miRNAs), especially in cancer, where global 3′UTR shortening accelerates disease progression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 38 publications
2
76
0
Order By: Relevance
“…The MACE technology, however, that was applied for the first time for the analysis of the transcriptome responses of plants to an infection by fungal pathogens delivers a complete overview of the regulation of almost all genes active in the infected leaves. MACE has been successfully applied in medical research (Müller et al, 2014; Zawada et al, 2014; Nold-Petry et al, 2015) and for the analysis of the translation and stability of messenger RNA (Müller et al, 2014). As we demonstrate here, it is also well suited to characterize defense mechanisms and hint to candidate resistance genes in plants.…”
Section: Discussionmentioning
confidence: 99%
“…The MACE technology, however, that was applied for the first time for the analysis of the transcriptome responses of plants to an infection by fungal pathogens delivers a complete overview of the regulation of almost all genes active in the infected leaves. MACE has been successfully applied in medical research (Müller et al, 2014; Zawada et al, 2014; Nold-Petry et al, 2015) and for the analysis of the translation and stability of messenger RNA (Müller et al, 2014). As we demonstrate here, it is also well suited to characterize defense mechanisms and hint to candidate resistance genes in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Poly(A) sites from the APADB database 50 were identified within the 3′-UTR regions of Ensembl protein-coding genes. For genes with multiple poly(A) sites, any pairs of poly(A) sites are defined as the end of the 3′ termini of common and extended 3′ UTR (the different region between longer 3′ UTR and shorter 3′ UTR) segments.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, using polyadenylation sites from APADB 26 and PolyASite databases 27 , we found that mRNAs encoding EMF proteins bear a higher number of alternative polyadenylation (APA) sites in 3'UTRs than mRNAs encoding the other groups of proteins ( Supplementary Fig. 1), even when accounting for the observed differences in 3'UTR length between the protein groups, by calculating the number of APA sites per kb ( Fig.…”
Section: Emf Proteins As a Model To Study The Regulation Of Protein Lmentioning
confidence: 99%